Distribution of Malaria Disease in Provinsi Kalimantan Timur, Indonesia - Empang Sari; Wa Dianti; Wa Ode Aini Zahra; Wahyuni Windi Aprita; Sukarni; Syahwa Syahbila Mussakina (Journal of Epidemiology and Health Science, 2025)
Background: Malaria is a life-threatening irresistible illness transmitted to people through the nibble of an tainted female Anopheles mosquito. It is commonly found in tropical regions and is both preventable and curable. East Kalimantan Province continues to face significant challenges in reducing malaria incidence. Individual and environmental factors play important roles in shaping community health status, including the spread of this disease. Objective: This study aims to describe the distribution of malaria disease in East Kalimantan Province, Indonesia, during the 2017–2020 period based on secondary data from the Central Bureau of Statistics of East Kalimantan. Methods: A quantitative descriptive approach was used with secondary data analysis obtained from the East Kalimantan Statistics Bureau. The data analyzed included the number of malaria suspects, confirmed malaria cases, and malaria-related deaths. Data were organized into tables and graphs and analyzed narratively to identify patterns and trends. Results: Findings indicate a significant decline in malaria suspects during the 2017–2020 period, likely due to government interventions such as the distribution of insecticide-treated bed nets in endemic areas. However, the number of confirmed malaria cases fluctuated annually without a consistent upward or downward trend. Meanwhile, the number of malaria-related deaths remained relatively low and stable over the last three years. Conclusion: The distribution of suspected malaria cases showed a significant decrease, most likely influenced by government interventions. Nevertheless, the fluctuating number of confirmed cases suggests that transmission still occurs in the community. Environmental factors and public behavior, such as low adherence to using bed nets, contribute to the continued spread. Despite this, the mortality rate remained low, reflecting improvements in healthcare services.